Response of FcεRI‐bearing leucocytes to omalizumab in chronic spontaneous urticaria. Issue 3 (7th February 2020) - Alizadeh Aghdam, Mehran; Knol, Edward F.; van den Elzen, Mignon; den Hartog Jager, Constance; van Os‐Medendorp, Harmieke; Knulst, André C.; Otten, Henny G.; Röckmann, Heike
Abstract: Background: The pathogenesis of chronic spontaneous urticaria (CSU) and the mechanism of action of omalizumab in CSU remain unclear. Objective: In this study, we assessed the responsiveness and FcεRI expression of various subsets of leucocytes in patients with CSU treated with omalizumab. Methods: In this prospective cohort study, 30 patients were treated with 6 administrations of 300 mg omalizumab every 4 weeks, followed by a follow‐up period of 12 weeks. FcεRI expression and the percentage of basophils, monocytes, and dendritic cell subsets were analysed before and during treatment, and after follow‐up. In addition, anti‐IgE– and C5a‐induced basophil degranulation was measured. The results were correlated with disease activity and response to omalizumab. Results: In addition to a rapid and significant reduction in FcεRI on basophils, we demonstrated a reduction in FcεRI on plasmacytoid dendritic cells during omalizumab treatment, which persisted until 3 months after discontinuation. FcεRI expression on basophils and its reduction did not correlate with the treatment response. Omalizumab led to an increased percentage of basophils in blood but not of the other FcεRI‐bearing leucocytes. Basophil responsiveness was differentially affected; anti‐IgE–, but not C5a‐induced basophil degranulation increased during the treatment. Apart from clinical non‐responders showing a stronger increase in anti‐IgE–induced basophil degranulation over a period time, no differences were found in omalizumab responders vs non‐responders. Conclusions/Clinical Relevance: FcεRI expression on basophils decreased rapidly, while anti‐IgE–induced degranulation significantly increased due to omalizumab treatment in patients with CSU, persisting at least for 3 months after stopping the treatment. None of the markers were able to predict the effectiveness of treatment. Whether basophils play a role in omalizumab responsiveness in CSU remains unclear.